Accuracy of point-of-care tele-ultrasonography for assisting ultrasound-naive resident doctors in detecting lower-limb deep venous thrombosis: A prospective controlled trial. (August 2022) - Bo, Xiao-Wan; Sun, Li-Ping; Wan, Jing; Sun, Yi-Kang; Zhang, Ya-Qin; He, Tian; Qian, Zhe-Bin; Qin, Chuan; Guo, Le-Hang; Xu, Hui-Xiong
Abstract: Objectives: This study aimed to explore the accuracy of point-of-care tele-ultrasonography (POC-TUS) in detecting lower-limb deep venous thrombosis (DVT). Methods: We conducted a prospective study in the intensive care unit (ICU). Each patient underwent three sessions of POC-US by one US-naive resident doctor (Group 1), one resident doctor supervised by a remote experienced radiologist through real-time POC-TUS (Group 2), and one on-site experienced radiologist (Group 3). The presence and location (if any) of lower limb DVT and the duration of examination of each patient were recorded. Diagnostic accuracy was determined by the consensus of two independent observers. Results: Finally, 71 patients (39.4%, 71/180) with lower limb DVT were identified. The accuracy of Group 2 was similar to that of Group 3 (91.7% vs. 92.8%, P =  0.694) but significantly higher than that of Group 1 (91.7% vs. 72.8%, P <  0.001). The median duration of examination of Group 2 (7 min) was shorter than that of Group 1 (11 min) ( P <  0.001) and longer than that of Group 3 (4 min) ( P <  0.001). Conclusion: Resident doctors can promptly and accurately detect lower-limb DVT in patients in the ICU with real-time POC-TUS guidance. Significance: Lower-limb DVT is the most common cause of pulmonary embolism and may result in substantial morbidity and mortality, and its early and accurate detection is crucial. This study is among the few to provide evidence for the usefulness of real-time POC-TUS early and accurate detection of lower-limb DVT.